Tunable micro-optofluidic prism based on liquid-core liquid-cladding configuration - Song, Chaolong (2012)
The integration of optical components into microfluidic systems has the potential to reduce the amount of bulky external devices and thus reduce the cost. However, one of the challenges of this concept is the accurate alignment of the optical path among multiple optical components inside a chip. We propose a tunable micro-optofluidic prism based on the liquid-core liquid-cladding structure formed in a sector-shape chamber. The optical interface of the prism is maintained in a straight line shape by distributing a row of pressure barriers in the chamber. By adjusting the flow rate ratio between core and cladding streams, the apex angle of the prism can be tuned accordingly. As a consequence, the deviation angle of the light beam refracted by the prism can be changed continuously. This tunability of our optofluidic prism can be utilized for the alignment of the optical path inside a chip or for the development of optical switches.